Neuromuscular changes and the rapid adaptation following a bout of damaging eccentric exercise. (5th January 2017) - Goodall, S.; Thomas, K.; Barwood, M.; Keane, K.; Gonzalez, J. T.; St Clair Gibson, A.; Howatson, G.
Abstract: Introduction: An initial bout of eccentric exercise is known to protect against muscle damage following a repeated bout of the same exercise; however, the neuromuscular adaptations owing to this phenomenon are unknown. Aim: To determine whether neuromuscular disturbances are modulated following a repeated bout of eccentric exercise. Methods: Following eccentric exercise performed with the elbow flexors, we measured maximal voluntary force, resting twitch force, muscle soreness, creatine kinase (CK) and voluntary activation (VA) using motor point and motor cortex stimulation at baseline, immediately post‐exercise and at 1, 2, 3, 4 and 7 days post‐exercise on two occasions, separated by 3 weeks. Results: Significant muscle damage and fatigue were evident following the first exercise bout; maximal voluntary contraction (MVC) was reduced immediately by 35% and remained depressed at 7 days post‐exercise. Soreness and CK release peaked at 3 and 4 days post‐exercise respectively. Resting twitch force remained significantly reduced at 7 days (−48%), whilst VA measured with motor point and motor cortex stimulation was reduced until 2 and 3 days respectively. A repeated bout effect (RBE) was observed with attenuated soreness and CK release and a quicker recovery of MVC and resting twitch force. A similar decrement in VA was observed following both bouts; however, following the repeated bout there was a significantly smaller reduction in, and a faster recovery of, VA measured using motor cortical stimulation. Conclusion: Our data suggest that the RBE may be explained, partly, by a modification in motor corticospinal drive.